#### Answer

9

#### Work Step by Step

Using order of operations, first solve parentheses, then exponents, then multiply, and last add.
5 + 2[$(7-5)^{2}$ + (1 - 3)] = 5 + 2[$(2)^{2}$ + (1 - 3)] = 5 + 2[4 + (1 - 3)] = 5 + 2[4 +(-2)] = 5 + 2[2] = 5 + 4 = 9

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

9

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.